The Development of Religious Moderation among Adolescents: An Islamic Education Perspective - Nurteti, Lilis; Endang, Ujang; Yasin, Alifa Irna; Lesmana, Belda Nurmultiefa (Bestari, 2023)
This study seeks to provide a detailed analysis of the progression of religious moderation in adolescents. This study employs a descriptive methodology. The approach of literature review was employed for data collecting. The collected data include hypotheses, empirical evidence, and documentation pertaining to the cultivation of religious moderation among adolescents. Data analysis utilizes interactive analysis, which is a method derived from the outcomes of inquiries and responses, written records, and conclusions to enhance comprehension. The cultivation of religious moderation among youths is a valuable resource for the state's future. Indonesia, as the largest Islamic country globally, should serve as an example for other nations in fostering genuine unity and moderation among teenagers. This is particularly crucial for Islamic Religious Education instructors, who have the responsibility of meeting this need. The responsibility of Islamic religious education teachers is to cultivate a mindset that is moderate and non-radical, and to address all issues in a balanced and inclusive manner.